Bioactive silver nanoparticles derived from Carica papaya floral extract and its dual-functioning biomedical application - E. S. Harsha Haridas; M. K. Ravi Varma; Goutam Kumar Chandra (Scientific Reports)
Abstract Replacing synthetic phytochemicals with natural plant extracts for metal nanoparticle synthesis enable cost-effective, large-scale production with reduced environmental and health risks while enhancing biomedical efficacy. This study presents the green synthesis of silver nanoparticles (AgNPs) using a flavonol-enriched extract from male papaya flowers (KQE), an underutilized agricultural waste. Using 20% (v/v) KQE, highly stable, spherical KQ-AgNPs (12.3 ± 3.0 nm) were synthesized via in-situ generation of free radicals, such as ortho-quinones, which reduced Ag+ ions. KQ-AgNPs exhibit superior antibacterial activity against both gram-positive and gram-negative bacteria compared to chemically synthesized AgNPs (AgNPs-Chem) and KQE alone. In vitro anticancer assays reveal enhanced cytotoxicity against breast carcinoma cells (MCF-7) with an IC50 of 21.25 ± 1.14 µg/mL, significantly lower than AgNPs-Chem (33.05 ± 3.13 µg/mL), while maintaining high biocompatibility with normal cells (HEK-293) with a greater IC50 of 169.96 ± 2.3 µg/mL. This study highlights the dual therapeutic potential of KQ-AgNPs, emphasizing their enhanced antibacterial and anticancer efficacy while exemplifying an innovative waste-to-wealth approach.